Computerized Adaptive Testing for Schizotypal Personality Disorder: Detecting Individuals at Risk - Li, Yaling; She, Menghua; Tu, Dongbo; Cai, Yan (Frontiers in Psychology, 2021)
As Schizotypal Personality Disorder (SPD) increasingly prevails in general population, a rapid and comprehensive measurement instrument is imperative to screen individuals at risk for SPD. To address this issue, we aimed to develop a Computerized Adaptive Testing for SPD (CAT-SPD) using a non-clinical Chinese sample (N=999), including calibration sample (N1=497) and validation sample (N2=502). The item pool of SPD was constructed from several wide-used SPD scales and statistical analyses based on Item Response Theory (IRT) via a calibration sample using Graded Response Model. Finally, 90 items, which measured at least one symptom of diagnostic criteria of SPD in the fifth edition of the Diagnostic and Statistical Manual of Mental Disorders and had local independence, good item-fit, high slope, no differential item function (DIF), composed the final item pool for CAT-SPD. In addition, a simulated CAT was conducted in an independent validation sample to assess the performance of CAT-SPD. Results showed that CAT-SPD not only had acceptable reliability, validity and predictive utility, but also had shorter but efficient assessment of SPD which can save significant time and reduce the test burden of individuals with less information loss.